2011
DOI: 10.4161/rna.8.5.16034
|View full text |Cite
|
Sign up to set email alerts
|

Two common SNPs in pri-miR-125a alter the mature miRNA expression and associate with recurrent pregnancy loss in a Han-Chinese population

et al.

Abstract: (2011) Two common SNPs in pri-miR-125a alter the mature miRNA expression and associate with recurrent pregnancy loss in a Han-Chinese population, RNA Biology, 8:5,[861][862][863][864][865][866][867][868][869][870][871][872]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 27 publications
5
91
0
Order By: Relevance
“…Many factors such as, uterine irregularity, chromosomal anomalies, endocrine dysfunctions, hematopoietic disease, immunological dysfunctions, lifestyle, and chronic maternal diseases, have been described that correlated to the abortion (2). The previous investigation indicated that two to seven-fold increase prevalence of RPL between the firstdegree blood relatives compared to the background community (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors such as, uterine irregularity, chromosomal anomalies, endocrine dysfunctions, hematopoietic disease, immunological dysfunctions, lifestyle, and chronic maternal diseases, have been described that correlated to the abortion (2). The previous investigation indicated that two to seven-fold increase prevalence of RPL between the firstdegree blood relatives compared to the background community (3).…”
Section: Introductionmentioning
confidence: 99%
“…The previous investigation indicated that two to seven-fold increase prevalence of RPL between the firstdegree blood relatives compared to the background community (3). Unexplained RPL is a stressful status of the couple, which assistance effort to overwhelming of the matter (2). It is estimated that approximately 50% of etiology of RPL cases remain unexplained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mature MIR423 level was lower in the C/A heterozygosity of rs6505162 than in the A allele, it was significantly increased by the C/A heterozygosity of rs6505162 as compared to the CC homozygote. These results suggest that the rare allele A in pre-MIR423 contributes to the production of mature MIR423, which is similar to the polymorphisms of MIR125A and has been shown to be associated with an increased risk of RPL in the Han Chinese population (Hu et al 2011). The rs6505162 C OA in MIR423 has been identified as a biomarker for many diseases.…”
Section: Discussionmentioning
confidence: 55%
“…Increasing evidence has shown that single nucleotide polymorphisms (SNPs) or mutations in miRNA coding regions may alter miRNA expression and/ or maturation, which may affect the occurrence of diseases (Saunders et al 2007, Jazdzewski et al 2008. Our previous report (Hu et al 2011) showed that two SNP sites in the pre-MIR125A coding region are related to human RPL, which means that miRNAs might play an important role in the occurrence of RPL.…”
Section: Introductionmentioning
confidence: 99%